The Applications of Mamdani Fuzzy in Water Selection of Pangas Catfish Ponds - Adi, Rizki Mugi Setya; Michelli, Laureta Mauren; Alkori, Hardian; Ramadhan, Rexy Gilang (Journal of INISTA, 2024)
In the field of fisheries, the selection of ponds water for Pangas catfish is very important because it affect the production and quality of fish. The purpose of this research is to apply the Mamdani fuzzy method in selecting suitable ponds water for Pangas catfish. The method used includes collecting data on water quality and environmental conditions, constructing the Mamdani fuzzy system and evaluating the results of selecting ponds water. The results of the study show that the Mamdani fuzzy method is able to provide a good solution in selecting ponds water for Pangas catfish by combining several factors such as temperature, pH and oxygen solubility. This concept can be used as a consideration in selecting the right ponds water for Pangas catfish so as to increase fish production and quality.